Pasca Perang Dagang Amerika Serikat dan China: Analisis Dampak pada Kebijakan Investasi Asing di Indonesia - Kristanti, Lisa; Rahayu, Sang Ayu Putu (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study analyzes the impact of the post-US-China trade war on foreign investment policy in Indonesia. Through a qualitative approach with normative research methods, this study examines the changes in the direction of investment policy in Indonesia that occurred in response to global geopolitical and economic dynamics. The results of the study show that the easing of trade tensions between the two superpowers has created a strategic momentum for Indonesia to reposition its position in the global investment ecosystem. The manufacturing, digital, and renewable energy sectors are the main magnets for foreign investment, indicating Indonesia's transition to a high-value-added economy. The implementation of adaptive investment policies, the development of Special Economic Zones that are integrated with global needs, and the implementation of the Job Creation Law act as catalysts in increasing Indonesia's investment competitiveness. This study concludes that the formulation of investment policies that are responsive to changes in geopolitical dynamics can transform global challenges into opportunities for sustainable national economic growth.